Extreme lateral interbody fusion (XLIF) approach for L5-S1: Preliminary experience - Xu, Junjie; Chen, Enliang; Wang, Le; Zou, Xiaobao; Deng, Chenfu; Chen, Junlin; Ma, Rencai; Ma, Xiangyang; Wu, Zenghui (Frontiers in Surgery, 2022)
Study Design: Technical report. Objective: Evaluate technical feasibility of extreme lateral interbody fusion (XLIF) at the L5-S1 level and provide an elaborate description of the surgical technique. Summary of Background Data: With the development of surgical techniques, the indications for oblique lumbar interbody fusion (OLIF) surgery have been broadened to the L5/S1 segment. However, this technique also has limitations. Different from OLIF, the L5/S1 segment used to be considered the main contraindication for XLIF. To date, no authors have reported the application of XLIF at the L5/S1 level. Methods: Only patients whose preoperative lumbar MRI showed the position of the psoas major muscles and blood vessels at the L5/S1 level were similar to those seen at supra-L5 levels were seleted. By folding the operating table, the iliac crest was moved downward to expose the L5/S1 intervertebral space during the operation. The remaining surgical procedures were consistent with routine XLIF surgery. Results: 8 patients successfully underwent XLIF at the L5/S1 level. The L5/S1 disk spaces were always exposed sufficiently for disk preparation and cage insertion. The post operative radiographs showed a satisfactory L5/S1 reconstruction with good cage position. Only 1 patient (12.5%) felt thigh numbness, and the symptoms gradually resolved after surgery and were no longer present in a month. There were no cases of psoas hematoma, retrograde ejaculation or vascular injury. The postoperative VAS score showed that all the patients achieved satisfactory results. Conclusions: XLIF at L5-S1 is feasible in strictly selected cases after thorough preoperative preparation and careful intraoperative procedures. However, we did not recommend XLIF as a routine surgical option at the L5/S1 level.